The Centrality of Kyai in Establishing Moderate Understandings in Salafiyyah Pesantren - Anis Humaidi; Najihatul Fadhliyah; Sufirmansyah Sufirmansyah (Nazhruna: Jurnal Pendidikan Islam, 2024)
The yellow book as a compulsory curriculum in Salafiyyah Islamic boarding schools includes intolerant teachings, especially in the chapters of jihad and hudud. However, the students at this pesantren showed extraordinary tolerance and avoided cases of religious violence. This sketch shows that the students did not just learn and explicitly follow the teachings of centuries-old religious texts. This article reveals the guidance of kyai (Islamic religious leaders) in shaping the attitude of tolerance of students through the interpretation of the yellow book. With a qualitative approach in the form of a case study, this study interviews the kyai who act as supervisors and teachers at the Sabilurrosyad Islamic boarding school in Malang. The findings of the study revealed that the kyai consistently guided their students in understanding classical texts based on their socio-cultural background, by emphasizing obedience to the government, respecting local wisdom, considering social conditions, and maintaining tolerance of other religions. In conclusion, kyai plays an important role as an interpreter of the yellow book so that students have a moderate understanding.